(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today, land use and land cover change have become crucial components of environmental monitoring and management strategies. A land cover mapping and monitoring was performed in the study area, namely the Kavathe Mahankal Tehsil of Sangli district, Understanding the causes and consequences of overexploitation of soil and water resources is necessary to maintain the current natural resources. For this study, LU/LC supervised classification was carried out using satellite images taken between March 2001 and March 2021. LULC classes were divided into five for the purpose of classification. The accuracy assessment is based on the classification error matrix and the KAPPA analysis. The land use and land cover classes were compared to detect changes between images. The largest land cover category was agricultural land, with 594.83 km2 in March, 2001 and 640.40 km2 in March, 2021.Vegetation is the second most extensive land cover category, covering 114.24 km2 in 2001 and 63.76 km2 in 2021. In the study, there were significant changes in all categories except for agriculture, vegetation cover, fallow land, and water bodies. A significant differential growth can be seen from the Built-up area, which increased from 0.128% in 2001 to 3.337% in 2021. Based on the classification methodology, the accuracy of the images of 2001 and 2021 is 81.24% and 78.96%, respectively, and Kappa statistics are 0.78 and 0.76, respectively.